2014
DOI: 10.1590/1809-4503201400060004
|View full text |Cite
|
Sign up to set email alerts
|

Equitable access to health services for children aged 5 to 9 in a medium city of northeasth of Brazil: a result of Family Health Strategy

Abstract: The study showed that access to health services has been relatively equitable through the FHS, a point of entry to the local health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Authors have published these studies between 1999 and 2017 (median: 2009) 5,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37 (Table 1). The authors of five studies reported having no conflicts of interest 19,28,31,33,35 , while in the other studies the authors did not disclose whether they had any conflicts of interest, nor did they examine interviewers' biases (in qualitative studies).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Authors have published these studies between 1999 and 2017 (median: 2009) 5,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37 (Table 1). The authors of five studies reported having no conflicts of interest 19,28,31,33,35 , while in the other studies the authors did not disclose whether they had any conflicts of interest, nor did they examine interviewers' biases (in qualitative studies).…”
Section: Resultsmentioning
confidence: 99%
“…While some studies had national coverage 5,12,13,14,22,24,25 , others covered certain geographical regions (e.g., Northeast or Southeast) 8,11,15,20,26 , states 16,33 , metropolitan areas 9,17,18 , municipalities 10,19,21,23,27,28,30,31,34,35,36,37 or parts of a municipality 22,32 . The study population included varied age groups, but most of them showed a balanced gender composition, with the exception of one study about men's health 37 and two about women's health 19,31 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations